Chandlerian firms vs. entrepreneurship - Alfonso Gambardella; Marco S. Giarratana (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2004)
This paper employs an original dataset for 146 US metropolitan areas to test some propositions that characterize two different models of organizing firms and industries: the managerial firm, epitomized by the work of Alfred Chandler, and the entrepreneurial system, recently highlighted by many authors. We discuss the reasons why, compared to the entrepreneurial systems, the Chandlerian world entails a lower spread of managerial salaries, greater product diversification, and a greater degree of products exploitation vs exploration. If there are knowledge spillovers, the entrepreneurial model produces higher expected managerial salaries. By providing systematic evidence about their characteristics, our study contributes to our understanding of the nature, the comparative advantages, and the potential division of labor between the two models.
Keywords: L2; M13; J3; 330; Chandlerian Firms; Entrepreneurship; Diversification; Technology; Entrepreneurship-Ansatz; Unternehmensorganisation; Diversifikation; Großstadt; USA